Miss Tjitjih Arts Building as a Center for Cultural Expression and Empowerment of the Betawi Arts Community - Shyabina Rahma Fasha; Nur Kharismawati Utami; Christanti Nugraheni (Department of Architecture, Faculty of Engineering and Computer Science, Universitas Muhammadiyah Semarang, 2026)
The Miss Tjitjih Art Building is a historic structure with high cultural and aesthetic value. As a symbol of Betawi art, this building integrates traditional elements with modern technology in its material concept and architectural expression. Its establishment was motivated by the large number of artists in the surrounding area and aims to preserve local art while improving the community's quality of life. The building provides a space for artistic expression, appreciation, and empowerment through its functional design. As a cultural hub, it encourages social and economic growth based on the arts community. This research employs a descriptive qualitative method, collecting data through observation, literature study, and documentation. The objective is to investigate the quality of life of the community around the Miss Tjitjih Art Building. The findings reveal that the presence of this art building has the potential to improve both the quality of life and the economy of the local community, as most artists and residents depend on income generated from these artistic activities.